INTERFERENSI GRAMATIKAL BAHASA MELAYU PONTIANAK TUTURAN BAHASA INDONESIA SISWA SDN 10 PONTIANAK UTARA - Tri Fika Putri Fadillah; Deden Syarani; Agus Syahrani (Universitas Tanjungpura, 2022)
ABSTRACTThis study analyzes language interference. The interference of Pontianak Malay language into Indonesian in the speech of SDN 10 North Pontianak students was chosen as the object with the aim of knowing clearly the description of grammatical interference. The problem discussed is about the form of grammatical interference, types of grammatical interference and factors. The data in this study are in the form of words, phrases, and sentences contained in the grammatical interference of language. The technique used in data collection is the listening method with tapping and note-taking techniques. Based on the results of the study, it was found that the types of grammatical relationship interference included the forms found in this study, namely (1) BMP interference in the wording in BI sentences, (2) particle interference ee, (3) particle interference ke, (4) interference lama particles, (5) interference of particles membuat, and (6) interference of changing the function of replica morpheme which is equivalent to the noun lok. The factor of the occurrence of language disorders is students' bilingualism in daily communication both with family, teachers, and school friends.Keywords: Interference, Grammatical Malay Language